Work conditions and determinants of health status among industrial shift workers: a cross-sectional study - Javanmardi, Sasha; Rappelt, Ludwig; Baumgart, Christian; Niederer, Daniel; Heinke, Lars; Freiwald, Jürgen (Frontiers in Public Health, 2025)
IntroductionThis study investigated potential health status differences among forging, manufacturing, and logistics workers.MethodsWe included 403 participants (age: 41 ± 12 years) from a medium-sized steel company (forge: 64, manufacturing: 299, logistics: 99). Health status was multifactorial assessed: (1) Frequency of musculoskeletal complaints (German Pain Questionnaire). (2) Pain intensity, physical and psychological load [visual analog scales (VAS) 0–100 points]. (3) Occupational moderate-to-vigorous physical activity (MVPA), total MVPA, and sedentary behavior [Global Physical Activity Questionnaire (GPAQ)]. (4) Quality of life [Short Form Health Survey (SF-36)]. Between-group effects were analyzed via one-way ANOVAs with post-hoc Tukey correction.Results308 workers (76.4%) reported at least one musculoskeletal issue. A significant between-group difference was revealed for left shoulder [F(2,40) = 5.40; p = 0.008; ω2 = 0.17], occupational MVPA [F(2,368) = 9.49; p < 0.001; ω2 = 0.04] and total MVPA [F(2,368) = 6.90; p = 0.001; ω2 = 0.03]. Post-hoc tests revealed a difference (p ≤ 0.007) between manufacturing (left shoulder: n = 22; 42.5 ± 24.8; occupational MVPA: n = 219; 6,978 ± 5,137 METs min/week; total MVPA: n = 219; 8,471 ± 5,390 METs min/week) and logistics workers (left shoulder: n = 14; 70.4 ± 26.3 au; occupational MVPA: n = 96; 9,640 ± 4,605 METs min/week; total MVPA: n = 96; 10,856 ± 4,680 METs min/week). No other between-group differences were observed.DiscussionVariations in health disparities across work conditions were observed. Yet, clear distinctions between work conditions and health outcomes remain a challenge. Effective interventions should be focused on job-specific and personalized health profiles rather than a stratification of work conditions to enhance health, productivity, and workforce sustainability.